GATA6 expression in Barrett's oesophagus and oesophageal adenocarcinoma. Issue 1 (January 2015) - Pavlov, Kirill; Honing, Judith; Meijer, Coby; Boersma-van Ek, Wytske; Peters, Frans T.M.; van den Berg, Anke; Karrenbeld, Arend; Plukker, John T.M.; Kruyt, Frank A.E.; Kleibeuker, Jan H.
Abstract: Background: Barrett's oesophagus can progress towards oesophageal adenocarcinoma through a metaplasia–dysplasia–carcinoma sequence, but the underlying mechanisms are poorly understood. The transcription factor GATA6 is known to be involved in columnar differentiation and proliferation, and GATA6 gene amplification was recently linked with poor survival in oesophageal adenocarcinoma. Aim: To study the expression of GATA6 during Barrett's oesophagus development and malignant transformation. To determine the prognostic value of GATA6 in oesophageal adenocarcinoma. Methods: Two retrospective cohorts were derived from the pathological archive of the University Medical Center Groningen. The first cohort contained 130 tissue samples of normal squamous epithelium, metaplasia, dysplasia and oesophageal adenocarcinoma. The second cohort consisted of a tissue microarray containing tissue from 92 oesophageal adenocarcinoma patients. Immunohistochemistry was used to examine GATA6 protein expression and to correlate GATA6 expression in oesophageal adenocarcinoma with overall and disease-free survival. Results: The percentage of GATA6-positive cells was low in squamous epithelium (10%) but increased progressively in Barrett's oesophagus (30%, P  < 0.001) and high-grade dysplasia (82%, P  = 0.005). GATA6 expression was not associated with overall or disease-free survival in oesophageal adenocarcinoma patients ( P  = 0.599 and P  = 0.700 respectively). Conclusion: GATA6 expression is progressively increased during Barrett's oesophagus development and its malignant transformation. However, no prognostic value of GATA6 expression could be found in oesophageal adenocarcinoma.